Synopsis of Potamogetonaceae in Iran with supplements to the Flora Iranica and a new identification key - Abbasi, Shabnam; Afsharzadeh, Saeed; Dinarvand, Mehri; Wiegleb, Gerhard (Phytotaxa, 2017)
Potamogetonaceae comprises three closely related genera: Potamogeton, Stuckenia and Groenlandia. The last comprehensive research on this species group in Iran dates back to 1971 (Flora Iranica). In this research we present an identification key to the Potamogetonaceae species in Iran with descriptions of all taxa based on morphological and anatomical studies. 11 species of Potamogeton, three species of Stuckenia and one of Groenlandia are described from Iran. Moreover, a new hybrid (P. pusillus × P. crispus) is described as a new to science. Distribution is outlined for all taxa. The genus Potamogeton and related genera have a wide distribution in different aquatic ecosystems in particular of northern, central and southwestern Iran. The species formerly recorded as P. alpinus was identified as P. schweinfurthii. It is recorded for the flora of Iran for the first time.